ANALISIS PENGARUH FAKTOR MOTIVASI, STRES KERJA, GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA - Nova P, Anita; Kurniawanto, Hudi; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
This study aims to analyze the effect of motivation, stress, leadership gays and work environment on employee performance. The purpose of this study was to analyze the significance of the influence of motivation, stress, leadership style and working environment factors on the performance of the state civil service. To analyze employee performance in reflecting influence of motivation, stress, leadership style an working environment factors on the performance of the state civil service. This study uses survey methods, the type of data used is quantitative, using approach aimed at testing hypotheses, the source of the data used are primary data. The population in this study were all employees of the Department of population and Civil Registration in Ponorogo Regency amounting to 64 people, the number of samples used was 50 employees, because the number of objects is less than 100 people so this research study is population study. This research was conducted by question. Data analysis techniques used validity test, reliability test, classic assumption test, normality test, heteroscedasticity test, multiple linear regression test, t test, F test. The conclusion of the study is: (1) hypothesis which states that work motivation has a significant effect on employee performance is not proven true, (2) hypothesis which states that work stress has a significant effect on employees is not proven true, (3) hypothesis which states that the leadership style has a significant effect on employees is proven to be true, (4) hypothesis which states that work environment has a significant effect on employees is not proven true.